The Role of Dietary Fiber or Prebiotics in Atopic Dermatitis - Marsha Kurniawan; Franklind Matthew (World Nutrition Journal, 2023)
Introduction: Atopic Dermatitis (AD) is a chronic inflammatory skin condition with itchy eczematous lesions, mostly found in children, and may affect a patientâ€™s quality of life. Individuals with AD were found to have dysbiosis of gut microbial, which may alter the immunologic tolerance of mucosa, causing inflammation and affecting skin conditions. Dietary fiber or prebiotics consumption may have a role in reversing dysbiosis and may affect AD. In this literature review, the authors would like to further explore the role of dietary fiber or prebiotics in the prevention and severity of AD/ Methods: Relevant literature research was conducted in several sources: Pubmed, EBSCOHOST, Proquest, and Google Scholar, using keywords â€œatopic dermatitis, atopic eczema, dietary fiber, prebiotic, nutrition.â€ Studies published within the last 10 years were included. Discussions: Dietary fiber, particularly soluble fibers and those which can be fermented by gut bacteria (including prebiotics), plays a role in maintaining homeostasis of normal gut flora by producing SCFA, which increases the gut barrier, has anti-inflammatory properties, balances Th1/Th2 ratio, increases lymphocytes in gut-associated lymphoid tissues (GALT) system, and increases secretion of intestinal IgA. The role of dietary fiber/prebiotics in the prevention or decreasing rate of AD is still a matter of debate. Several studies showed no effect or correlation of prebiotic supplementation in decreasing the AD rate in pregnant women or babies with a high risk of atopy. On the other hand, several studies on prebiotic supplementation for babies and children have shown the benefits of prebiotic supplementation in preventing allergies (AD, rhinoconjunctivitis, and urticaria). Conclusion: The role of dietary fiber/prebiotics in preventing or treating AD is still a matter of debate. Different study results make it difficult to conclude the clinical effect of prebiotics in allergy prevention, particularly AD. This may be caused by the heterogeneous studies and the limited number of studies on humans. Further studies (RCT) involving large-scale respondents are needed to define the effects of prebiotic supplementation in the prevention or alternative therapy for AD.